The Effect of Time Variations in the Pure Aluminium Anodization Process - Paundra, Fajar; Irfan, Angga; Sidik, M.farhan; Pujiyulianto, Eko; Nurdin, Akhmad (ROTASI, 2024)
Aluminium is a white non-ferrous metal and is easily oxidized. In the industrial world, aluminium was chosen because it has the advantages of light density, corrosion resistance, easy fabrication (forged), high thermal and electrical conductivity. However, aluminium also has disadvantages, namely having a low hardness value when compared to steel. Pure aluminum hardness is only around 50 VHN. Therefore anodizing is expected to improve the hardness value of aluminium. This study aims to determine the effect of time variation on the value of changes in mass, hardness, oxide layer thickness, and microstructure. This study used aluminium 1100 with a time variation of 60, 70, 80, and 90 minutes, a concentration of H2SO4 of 10%, a current density of 6 A and a voltage of 20 V. The results of the study using a time variation of 60, 70, 80 and 90 minutes obtained the change in value the smallest mass occurred at 60 minutes of 0.4 g and the largest occurred at 90 minutes of 1.09 g. The smallest hardness value occurred at 60 minutes at 72.8 VHN and the highest occurred at 90 minutes at 86.7 VHN. The lowest layer thickness value occurred at 60 minutes of 7.96 µm and the highest occurred at 90 minutes of 10.79 µm